Improving parallel execution time of sorting on heterogeneous clusters - Cerin, C.; Koskas, M.; Fkaier, H.; Jemni, M. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2004: Anais do XVI Symposium on Computer Architecture and High Performance Computing, 2004)
The aim of the paper is to introduce techniques in order to optimize the parallel execution time of sorting on heterogeneous platforms (processors speeds are related by a constant factor). We develop a constant time technique for mastering processor load balancing and execution time in an heterogeneous environment. We develop an analytical model for the parallel execution time, sustained by preliminary experimental results in the case of a 2-processors systems. The computation of the solution is independent of the problem size. Consequently, there is no overhead regarding the sorting problem.